2017
DOI: 10.1371/journal.pone.0183488
|View full text |Cite
|
Sign up to set email alerts
|

Dual specificity phosphatase 6 deficiency is associated with impaired systemic glucose tolerance and reversible weight retardation in mice

Abstract: Here, we aimed to investigate the potential role of DUSP6, a dual specificity phosphatase, that specifically inactivates extracellular signal-regulated kinase (ERK), for the regulation of body weight and glucose homeostasis. We further assessed whether metabolic challenges affect Dusp6 expression in selected brain areas or white adipose tissue. Hypothalamic Dusp6 mRNA levels remained unchanged in chow-fed lean vs. high fat diet (HFD) fed obese C57Bl/6J mice, and in C57Bl/6J mice undergoing prolonged fasting or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In contrast, a recent study observed comparable body weight, fat and lean mass in DUSP6 −/− and DUSP6 +/+ mice after 26 weeks on a HFD. However, glucose tolerance was somewhat abnormal in both lean and obese DUSP6 −/− mice when compared to controls [ 157 ]. At present it is unclear why there is a discrepancy between the latter study and the previous two, but the finding that variations in the gut microbiota can have profound consequences for sensitivity to HFD coupled with differences in the genetic backgrounds used in these studies (pure C57Bl/6 J vs .…”
Section: The Cytoplasmic Erk-specific Mkpsmentioning
confidence: 99%
“…In contrast, a recent study observed comparable body weight, fat and lean mass in DUSP6 −/− and DUSP6 +/+ mice after 26 weeks on a HFD. However, glucose tolerance was somewhat abnormal in both lean and obese DUSP6 −/− mice when compared to controls [ 157 ]. At present it is unclear why there is a discrepancy between the latter study and the previous two, but the finding that variations in the gut microbiota can have profound consequences for sensitivity to HFD coupled with differences in the genetic backgrounds used in these studies (pure C57Bl/6 J vs .…”
Section: The Cytoplasmic Erk-specific Mkpsmentioning
confidence: 99%
“…DUSP6 expression is regulated transcriptionally ( Bermudez et al, 2011 ; Ekerot et al, 2008 ; Zhang et al, 2010 ), and post-transcriptionally by miRNAs ( Banzhaf-Strathmann et al, 2014 ; Carson et al, 2017 ; Gu et al, 2015 ) and RNA-binding proteins ( Bermudez et al, 2011 ; Galgano et al, 2008 ; Lee et al, 2006 ). Altered expression or activity of DUSP6 impacts on ERK signaling in various diseases such as cancer and neurological disorders ( Banzhaf-Strathmann et al, 2014 ; Bermudez et al, 2008 ; Kawakami et al, 2003 ; Li et al, 2007 ; Molina et al, 2009 ; Pfuhlmann et al, 2017 ; Shojaee et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a close relationship between metabolic disorders and macrosomia, and these infants may also suffered from disordered glucose metabolism and obesity in later life [ 3 , 26 , 27 ]. C MA-A2 included DUSP6 (dual specificity phosphatase 6), which is associated with lipid metabolism and glucose homeostasis [ 28 , 29 ]. It has been reported that CORO1C (coronin 1C) were highly expressed in adipose tissues, and it might be critical genes in the development and prognosis of obesity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%